Efektivitas Program Pelatihan Penetapan Tujuan pada Siswa Sekolah Menengah Atas - Jimny Hilda Fauzia; Farida Kurniawati (Jurnal Psikologi Teori dan Terapan, 2020)
Goal setting is an important skill for students to have so they can achieve academic success. This study aims to test the effectiveness of the goal setting training in improving students' knowledge and skills for setting goals. The study was a quasi-experimental design and was structured in experiential learning framework. The subjects were 12 students. Data were collected quantitatively using a questionnaires and qualitatively using observation and open-ended questions. The paired sample t-test was used to analyze quantitative data, while qualitative data were analyzed descriptively based on goal-setting concept. The results show that participants of this study experienced a significant increase in knowledge and skills scores after attending the training (p<0.001). The training process runs according to established procedures, so that training objectives can be achieved properly. The quality of the contents of the discussion and the answers of students in the test showed good results. However, this training still needs to be supplemented with follow-up to ensure changes in student behavior after attending the training. This study suggests that schools should facilitate their students to involve in goal setting trainings and activities in order to increase their opportunities in achieving academic success.Keywords: Goal setting, training, secondary studentsAbstrak: Penetapan tujuan merupakan salah satu keterampilan yang penting untuk dimiliki siswa agar mereka dapat mencapai kesuksesan akademik. Penelitian ini bertujuan untuk menguji efektivitas pelatihan penetapan tujuan untuk meningkatkan pengetahuan dan keterampilan siswa dalam menetapkan tujuan. Penelitian dilakukan dengan desain kuasi-eksperimental dan disusun dengan kerangka experiential learning. Subjek penelitian ini adalah 12 orang siswa Sekolah Menengah Atas (SMA) œSukses Jakarta. Data dikumpulkan secara kuantitatif dan kualitatif. Analisis data kuantitatif dilakukan dengan teknik paired sample t-test, sedangkan analisis data kualitatif dilakukan dengan mengumpulkan data observasi selama pelatihan berlangung dan meninjau kualitas jawaban siswa pada tes. Hasilnya menunjukkan bahwa siswa mengalami peningkatan skor pengetahuan dan keterampilan yang signifikan (p<0,001) setelah mengikuti pelatihan. Proses pelatihan berjalan sesuai prosedur yang telah ditetapkan, sehingga tujuan pelatihan dapat tercapai dengan baik. Kualitas isi diskusi dan jawaban siswa dalam tes menunjukkan hasil yang baik. Namun demikian, pelatihan ini masih perlu dilengkapi dengan tindak lanjut untuk memastikan adanya perubahan perilaku siswa setelah mengikuti pelatihan. Hasil penelitian ini menunjukkan penting-nya bagi sekolah untuk memfasilitasi para siswanya mengikuti kegiatan dan pelatihan terkait penetapan tujuan demi tercapaianya keberhasilan akademik mereka.